Mindful Pedagogy: Invocating the Concept of Play Beyond the Confines of Recess - Blom, Rob; Lu, Chunlei; Mgombelo, Joyce (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2015)
Recess is often a topic overlooked in pedagogical theory due to its presumed simplicity. The essence of recess connects with play as a physical counterpart to a well-rounded education. In this article we explore the relationship play has with recess and well-being and explore its pragmatikos (systematic usefulness) as regards schooling in lieu of deep ecological frameworks of systems (wholism) theory and systemic, nonlinear dynamics. We argue that recess in its current conceptualisation—in contradistinction to work or study—is a counterfeit to metaphysical play based on the writings of Ananda K. Coomaraswamy who sheds light on its spiritual premise. By bringing to the forefront metaphysical Ideas of play we encounter similitudes between the Platonic doctrine of ēdūcere and anamnesis with Buddhist phenomenology, especially regarding the practice of Mindfulness (sati); both extol a “recollection” as opposed to a “memorisation” which arguably occupies much of Westernised curriculum. Finally, in traditional, premodern education, emphasis was placed on Spirit and heartfelt intuition, a remembrance of who we are, our Buddha-nature or Christhood, not on cerebral ratiocination whose mental operation, according to Plato, was tenebrous and illusory. Our aspiration is not an education that includes mindfulness, rather, a mindfulness-based education.